ImProving Outcomes after STroke (POST): Results from the Randomized Clinical Pilot Trial. Issue 8 (December 2013) - Hackett, Maree L.; Carter, Greg; Crimmins, Denis; Clarke, Tracy; Arblaster, Lucy; Billot, Laurent; Mysore, Jayanthi; Sturm, Jonathan
Background: One in three patients experience depression after stroke. An effective strategy to prevent depression after stroke that could be economically delivered to most patients with a low likelihood of adverse events is needed. Methods: In a randomized trial conducted in New South Wales, Australia, a postcard was sent monthly to participants ( n = 100) for five-months following hospital discharge after stroke (plus usual care) and compared with usual care ( n = 101). Ethical approval was obtained to withhold information about the intervention and primary outcome from participants during the consent process. Results: No significant difference was seen in the proportion of participants with depression in the intervention group (1/88) vs. the control group (3/76) (relative risk 0·29, 95% confidence interval 0·03–2·71) at six-months. No significant differences were seen on Hospital Anxiety Depression Scale (HADS) depression and anxiety sub-scale scores, quality of life, or activities of daily living; however, many (47/100) responded positively to the postcards. Conclusions: Although this simple postcard intervention did not significantly reduce the proportion of participants experiencing high HADS depression sub-scale scores after stroke, it may be an effective way to engage with people after stroke following hospital discharge.